Constraints on generality statements are needed to define direct replication. (27th July 2018) - Simons, Daniel J.; Shoda, Yuichi; Lindsay, D. Stephen
Abstract: Whether or not a replication attempt counts as "direct" often cannot be determined definitively after the fact as a result of flexibility in how procedural differences are interpreted. Specifying constraints on generality in original articles can eliminate ambiguity in advance, thereby leading to a more cumulative science.